A preview study on UWB imaging system to detect early breast tumor - Lakshmi, A. Naveena; Sabira, Khatun; AlShehri, S. A. (Springer Nature Switzerland, 2011)
Breast cancer is the second leading cause of cancer death after lung cancer among the women. In this paper we reviewed some breast cancer detection techniques like Mammography, Magnetic Resonance Imaging (MRI), ultra Sound and Ultra Wide Band (UWB) and its performances. Current UWB systems having some limitations including they are not able to detect the tumor at early stages, a multiple antenna array in terms of complex system and in all systems no pictorial 3D representation of tumor size. To overcome this limitation, a thorough investigation is done here, to find out the limitations of existing and proposed systems followed by the open issues which need to be resolved.